Mariama on the Move. Migration Capital and Second Generations in Spanish Youth Emigration - Narciso Pedro, Laia; Carrasco Pons, Sílvia (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2017)
Media representations of Spanish young adults leading a new emigration wave towards Europe in the last years usually picture by default a homogeneous group that does not match with the real flow. This paper contributes to make visible the diverse composition of Spanish youth who migrate abroad in the context of the economic crisis and their specific strategies based on ethnographic fieldwork carried out in the area of Barcelona. The analysis focuses on the case study of Mariama, the daughter of a West African family who migrated to Europe, and her community and emancipation mobility. Her trajectory and experiences show how migration capital is built and used to produce the emergence of a ‘new’ mobility project, while she joins that share of young Spaniards who have been forced to build their future in other European countries.